Stroke subtype, age, and baseline NIHSS score predict ischemic stroke outcomes at 3 months: a preliminary study from Central Nepal - Shrestha, Shakti (J Multidiscip Healthc, 2015)
BACKGROUND: The combined medications practice of using antithrombotic agents and statins with or without antihypertensive agents is common in the treatment of acute ischemic stroke in Nepal. Short-term outcomes of the current practice have been studied. We aim to explore the predictors of ischemic stroke outcomes at 3 months, with the current combined medications practice. METHODS: The study population (N=56) included acute ischemic stroke patients treated at the Neurology Department of the College of Medical Sciences-Teaching Hospital, Chitwan, Nepal, from May 2014 to August 2014 and followed up at 3 months. Death or disability (modified Rankin scale >2) was defined as poor outcomes. Multivariate logistic regression analysis (P<0.10) using potential variables from bivariate analysis (P≤0.20) was adjusted to predict outcomes at 3 months. RESULTS: At 3 months, 29 (51.8%) patients were independent, eleven (19.6%) were dependent, while 16 (28.6%) died. Stroke subtype and baseline National Institute of Health Stroke Scale (NIHSS) scores were associated with death/disability (27, 48.2%) at 3 months. Regression analysis showed that large-artery stroke (odds ratio [OR] =284.145, 95% confidence interval [CI] =5.221–15,465.136, P=0.006), age (OR =1.113, 95% CI =1.002–1.236, P=0.045), and baseline NIHSS score (OR =1.557, 95% CI =1.194–2.032, P=0.001) were significant predictors of poor outcome at 3 months. CONCLUSION: Stroke subtype, age, and baseline NIHSS score are predictors of ischemic stroke outcomes in Nepalese population treated with the current practice of using combined antithrombotic and statins with or without antihypertensive agents, and these predictors can be used for the improvement of selection of patients for the appropriate treatment.